Accuracy of Bicycle Counting with Pneumatic Tubes in Oregon. Issue 1 (2016) - Nordback, Krista; Kothuri, Sirisha; Phillips, Taylor; Gorecki, Carson; Figliozzi, Miguel
Interest in counting bicycles and establishing nonmotorized counting programs is increasing, but jurisdictions still struggle with how to integrate bicycle counting into standard practice. In this paper, the authors share findings and recommendations for how to minimize error for bicycle counting from tests conducted in conjunction with the Oregon Department of Transportation. This research studied three types of off-the-shelf pneumatic tube counters for counting bicycles, including equipment from five manufacturers: two bicycle-specific counters, three varieties of motor vehicle classification counters, and one volume-only motor vehicle counter. Tests were conducted both in a controlled environment and in on-road mixed traffic to better identify problems in accuracy. Equipment studied generally undercounted cyclists, especially those in groups. Results from the controlled test with standard bicycles showed that within 10 ft of the counter, the undercounting error ranged from 0% to −12%. In the mixed-traffic test, all the equipment tested tended to undercount with mean percent error ranging from −10% to −73%. Each counter type has pros and cons, but in general, counting accuracy decreased with increases in bicycle and motor vehicle traffic and longer tube lengths. Higher accuracy can be achieved by careful selection of equipment type, classification scheme, and tube configuration. Bicycle speeds given by off-the-shelf pneumatic counting equipment were accurate.